The Second Industrial Revolution and the Staples Frontier in Canada: Rethinking Knowledge And History - Hull, James (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1994)
ABSTRACTIn the late nineteenth century and the early twentieth century the exploitation of Canada's softwood forests was transformed by the new technologies of the second Industrial Revolution. This can be understood in terms of Innis's staple thesis as the exploitation of natural resources on a margin for and using the technology of a more advanced Euro-American centre. The sociology of knowledge also provides a framework for analysis as old and new bodies of technical knowledge were possessed by and altered the relationships among different social groups. Changes were experienced both in the woods (pulpwood logging) and in the mills (pulp and paper making) in ways which were broadly similar but different in timing and other significant respects.